Filmowcy amatorzy w Polsce przed rokiem 1939 - Hendrykowska, Małgorzata (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2017)
The article is devoted to the activities of Polish amateur filmmakers from the turn of the 19th and 20th centuries to 1939. The development of amateur filmmaking was closely tied to advancements in the production of cameras and film. The first attempts to create an organized amateur filmmaking movement were made in the 1930s, when clubs and associations began to be formed. During this period, Polish amateur filmmakers had their first successes at European and international film festivals and events. The author discusses the most valuable extant pre-war amateur documentaries, and follows the discovery of new films dating back to before 1939. She also relates the “second life” of the oldest amateur films, which have been incorporated into contemporary documentaries.